Clinical presentations of Sjogren's syndrome in Benghazi, Libya - Ahmed, Abdelnasir; Ibkhatra, Salem; Elbraki, Fathi; Ehsouna, Hamdi; Alsaeiti, Khaled (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Background: We aimed to characterize the clinical presentation of primary and secondary Sjögren's syndrome (SS) among patients in Benghazi, Libya. Patients and Methods: Sixty consecutive patients (55 females and 5 males) diagnosed with SS according to 2016 European–American consensus criteria were studied. Patients with chronic hepatitis C virus, human immunodeficiency virus infection, and previous lymphoproliferative processes were excluded. Results: The mean age at the time of diagnosis was 41.9 ± 9.9 years (25–56 years). Seventeen patients (28.3%) had primary SS (pSS). At diagnosis, commonly reported symptoms included dry mouth (52; 86.7%), dry eyes (55; 91.7%), dental caries (25; 41.7%), and oral candidiasis (20; 33.3%). Schirmer's test was positive in seven patients (11.7%). The most common extraglandular manifestations were arthralgia and arthritis (49; 81.7%), Raynaud's phenomenon (23; 38.3%), and interstitial lung disease (9; 15%). Both pSS and secondary SS (sSS) were associated with lymphocytosis. Abnormal thyroid disease was reported in 14 (23.3%). sSS was mostly associated with rheumatoid arthritis 28 (46.7%), followed by systemic lupus erythematosus 11 (18.3%). Fifty-three patients (88.3%) had positive rheumatoid factor (RF) and 18 patients (30%) had positive antinuclear antibodies (ANAs). RF was strongly associated with sSS and Sicca symptoms with P = 0.004 and 0.001, respectively, while ANA positivity was strongly associated with pSS and extraglandular manifestations (P = 0.001 and P = 0.003, respectively). Conclusions: This is the first series of SS from Libya. It should help understanding the characteristics and associations that should help understand the global picture.
Keywords: Antinuclear antibodies; autoimmune disease; rheumatoid arthritis; Sjögren's syndrome; systemic lupus erythematosus